Fiscal incentives for small enterprises and startups in Algeria -A comparative study- - chenati, Sami (Journal of Research in Finance and Accounting, 2024)
This study aims to compare the tax incentives for micro enterprises and start-up in the Algerian tax system, and to identify the concept of each of them according to various international organizations and according to the Algerian legislator, as well as the fundamental differences between them. The study concluded several results, the most important of which is the existence of fundamental differences between micro enterprises and start-up, especially with regard to the quality of the product that each of them provides, the size of the market in which it is active, and the quality of its investments and financing methods. The study also concluded that there are differences between the tax incentives approved by the Algerian legislator to stimulate both types. Of institutions, although the incentives in their entirety aim to support and accompany the success of micro enterprises and start-up.